The Influence of AI Chat GPT Technology on the Mindset of Educational Technology Students at Ibn Khaldun University, Bogor - Rudi Hartono; Ahmad Fauzan Ar Ridho; Faghia Rahma Zaki; Muhammad Faqih Al Ghifari (CV. Media Inti Teknologi, 2024)
This research aims to increase understanding of the influence of AI Chat GPT technology on the mindset of students in the Educational Technology Study Program at Ibn Khaldun University, Bogor. This research was conducted using quantitative research methods with data collection techniques through questionnaires. This research involved respondents consisting of Educational Technology students in semesters 1, 3, 5 and 7 at Ibn Khaldun University, Bogor. The results of this research show that AI Chat GPT technology can influence the mindset of students in the Educational Technology Study Program at Ibn Khaldun University, Bogor. This is evident from students' statements during the questionnaire that AI Chat GPT technology can influence students' mindsets. This research concludes that AI Chat GPT technology greatly influences the mindset of students in the Educational Technology Study Program at Ibn Khaldun University, Bogor. Therefore, it is hoped that students will pay more attention to using AI Chat GPT Technology in lectures.